THE EFFECT OF BRAND EQUITY, PROMOTION AND SERVICES ON CUSTOMER'S DECISION TO USE SHARIA BANK IN SANGKUMPAL BONANG PADANGSIDIMPUAN MARKET - jeni kurnia; muhammad isa; budi gautama; damri batubara (Journal Of Sharia Banking, 2020)
Sangkumpal Bonang market is the same as the market in general, where this market is where people trade, looking for fortune, a place where sellers and buyers meet and conduct transactions. Based on data obtained by Sangkumpal Bonang Padangsidimpuan market, more traders use conventional banks than sharia banks. This study aims to determine the effect of brand equity, promotion and service on customer decisions using Islamic banks in the Sangkumpal Bonang Padangsidimpuan market. This research is a quantitative research, data sources used are primary data. The data collection technique used was a questionnaire, and documentation with a total sample of 69 respondents with the sample measurement technique was the Slovin formula. The results of partial research (t test) are Brand Equity and Services affect the Customer Decision while Promotion does not affect the Customer Decision.